THE EFFECT OF 8-WEEK CORE TRAINING ON 100 M BACKSTROKE SWIMMING PERFORMANCE ON 13-15 AGE MALE SWIMMERS - Ahmet Gönener; Deniz Demirci; Utku Gönener; Beyza Özer; Ozan Yılmaz (ümit doğan üstün, 2017)
In this study, It was aimed to investigate the effect of 8-week core training on backstroke swimming style 100 m performance in male swimming group of 13-15 age group. 24 athletes from the Gebze Gençlerbirliği Swimming Club participated in this study. The groups are divided into experiment group and control group randomly as 12 persons per group. During the study, the experimental group participated in core training in addition to swimming for 3 days a week. Control group just participated in swimming training during the survey. The exercises were designed as strength training for core muscles for 8 weeks. 100 m swimming test was used as a test measurement tool. The obtained data from pre and post test comparison was analyzed with Wilcoxon Signed Ranks test in SPSS 21.0 statistical package program. When the pretest and posttest results were compared as intragroup, a statistically significant difference was found in the experimental group (p<.05). Nevertheless, there was no statistically significant difference in pretest-posttest comparison of the control group (p>.05). As a result, it was seen that the core area trained by 8-week core training on 13-15 age male swimmers have a positive effect on 100 m backstroke style performance.